Implementation of Husband's Maintenance Obligations to Wife in the Perspective of Compilation of Islamic Law as an Effort to Protect Wife's Rights - Nurin Sulfa Arafiah (Rechtsvinding, 2026)
The gap between normative legal provisions and social practices related to the fulfillment of husband maintenance is still a challenge in ensuring the protection of the wife's rights. This research aims to examine the concept of sustenance from the perspective of Islamic law, examine its arrangement in the Compilation of Islamic Law, and identify its implementation in people's lives. This study uses a normative juridical method with a legislative and conceptual approach supported by literature studies. The results of the study show that the Compilation of Islamic Law has clearly regulated the husband's obligations in providing maintenance, both material such as clothing, food, and board, as well as non-material such as affection and protection. However, its implementation in the community still faces various obstacles, including economic factors, low legal awareness, and not optimal law enforcement. In addition, social dynamics in the modern family also affect the understanding of maintenance obligations. This condition has an impact on the maximum fulfillment of the wife's rights. Therefore, systematic efforts are needed through increasing legal literacy, strengthening law enforcement mechanisms, and the active role of judicial institutions and related institutions to realize justice and welfare in the household.